Prevalence of human papillomavirus in tonsil brushings and gargles in cancer-free patients: The SPLIT study. (March 2017) - Combes, Jean-Damien; Dalstein, Véronique; Gheit, Tarik; Clifford, Gary M.; Tommasino, Massimo; Clavel, Christine; Lacau St Guily, Jean; Franceschi, Silvia; ,
Highlights: Prevalence of HPV infection in cancer-free tonsil tissue is low. Oral HPV infection is relatively common in adults. Agreement for HPV infection in paired tonsil brushings and gargles is low. Abstract: Objective: To evaluate human papillomavirus (HPV) prevalence in the tonsil using extensive ex vivo brushing and gargling in a large age-stratified sample of cancer-free patients. Materials and methods: From 2012 to 2016, consecutive patients undergoing tonsillectomy for benign indications in 19 French University Hospitals were invited to participate in the SPLIT study. Immediately after resection, half-tonsils were extensively brushed at the pathology laboratories on the surface epithelium and in tonsil crypts to collect exfoliated cells. In 11 centers, patients aged 15 and over (adults) were also asked to provide gargle samples before surgery. HPV-DNA detection used a very sensitive Luminex technology to evaluate 21 HPV types. Results: Tonsil brushings from 692 patients aged 1–70 years and gargles from 268 adults were tested for HPV. Among adults, overall HPV prevalence was 3.6% in tonsil brushings and 13.1% in gargles and HPV16 prevalence was 2.2% and 4.1%, respectively. Among 139 children, tonsil brushings were positive in two girls (1.4%). Percent agreement in HPV detection in paired tonsil brushings and gargles in adults was 85.8% and positive agreement 9.5%. HPV prevalence in gargles significantly varied by sex (prevalence ratio in men vs women = 2.1; 95% confidence interval; 1.1–4.1) and tonsillectomy indication (non-infectious vs. infectious = 4.9; 1.4–17.0). Conclusion: HPV infection is infrequent in tonsil brushings of cancer-free children and adults. In contrast, HPV infection in gargles in adults is rather common. Low agreement in paired tonsil brushings and gargles suggests that gargle is not representative of HPV prevalence in the tonsil.